Febuxsostat as a renoprotector in patients with chronic renal insufficiency - Z. V. Babenko (Kazimierz Wielki University, 2019)
In the article presented the data about dependence of uricemia's level and the subjective assessment of the quality of life in patients with end stage renal disease (ESRD) and an increase ofresidual functional renal reserve in 90 patients under the influence of febuxsostat at a dose of 40 mg are given. It has been proved that by reducing the level of uric acid, the residual functional renal reserve increases and the quality of life of patients improves (according to the questionnaire). This is best reflected in predialysis patients with ESRD. The data obtained allow febuxsostat consider to be effective urates-reductive therapy.